The Influence of the Service Marketing Mix on The Purchase Decision of The Tutoring of Ganesha Operation Cilegon City - Lola Monica Sumarto; Yulia Nur Hasanah (Budapest International Research and Critics University, 2022)
Education is one of the most important needs for humans. The growth of various tutorings has become an interesting phenomenon for the world of education in Indonesia. One of the tutorings whose existence is already widely known is Ganesha Operation (GO). This study aims to find out the influence of marketing newness on the purchasing decision of Ganesha Operation Tutoring in Cilegon City. The research method used is descriptive using quantitative methods involving 100 respondents of parents of Ganesha operation tutoring students in Cilegon City. The sampling technique used is non-probability sampling with a purposive sampling type. In this study, respondent data was processed using the SPSS 25 for Windows application. The results of the study based on a descriptive analysis for the marketing mix variable are already in the excellent category by 88% and the purchase decision variable is already in the very good category by 88%. The marketing mix had a positive and significant effect on purchasing decisions with a magnitude of influence of 67.2% and the remaining 32.8% influenced by other factors that were not studied.